Kepuasan pelanggan terhadap kualiti perkhidmatan kaunter: kajian perbandingan di jabatan imigresen dan jabatan pendaftaran negara - Bujang, Siti Mariam (2000)

(untitled)
Counter services quality is being considered as one of the most important research topics in the context of human resource development, since it closely relates to customer satisfaction. Employee apathy, lacks of knowledge and skill, inadequate service operation systems, inflated customer expectation are some reasons often attributed to poor service. Hence, this study was conducted to identify customer satisfaction towards counter services and the difference of counter services quality at Jabatan Imigresen and Jabatan Pendaftaran Negara. Four hundreds of seventy sets of questionnaires were received and analysed by using Statistical Package for Social Sciences (SPSS) software to achieve the outcome of the study. The findings show that customer’s expectation is high towards service quality that was delivered. However, the customer’s perception towards counter services that perceived from the organization is in moderate level. Based on the customer satisfaction, most of the customers have a moderate perception towards the quality of staff, equipments and facilities, work operation and communication behaviour. Furthermore, results also depict that there is no difference of counter services quality that received by the customers between both organizations. Four elements namely tangibility, reliability, responsiveness and assurance have showed that there is difference between customers perception towards counter services provided by both organizations. The result also shows that there is correlation between acquirement of counter services quality and customer satisfaction at Jabatan Imigresen. Meanwhile in Jabatan Pendaftaran Negara, the finding indicates that there is correlation between counter services quality and customer satisfaction based on elements of responsiveness, assurance and empathy. Several recommendations were suggested to both organizations in order to improve their counter services quality and also to achieve customer satisfaction.